Honey hydrogel dressing to treat burn wound in rats - a preliminary report - Mohd Zohdi, Rozaini; Abu Bakar @ Zakaria, Md Zuki; Yusof, Norimah; Mohamed Mustapha, Noordin; Somchit, Muhammad Nazrul; Hassan, Asnah (Universiti Putra Malaysia Press, 2012)
Various studies have shown that honey is effective in healing burns and wounds. In this study, Malaysian honey was incorporated into hydrogel dressing formulation using electron beam irradiation technique and introduced as Honey Hydrogel dressing. The wound healing efficacy of Honey Hydrogel dressing on deep partial thickness burns was monitored on the basis of gross appearances, rate of wound contraction and histopathological changes. Deep partial thickness burns were created by applying an aluminium template preheated to 85°C to the backs of rats for 5 s and randomly treated with Honey Hydrogel or hydrogel while control group received no treatment. Wound appearance was photographed and the rate of wound contraction was calculated at 7, 14, and 21 days post burn. Rats were euthanized after 21 days of treatment and skin samples were taken for histopathological examination. The wounds treated with Honey Hydrogel dressing showed better gross appearances and significantly (p<0.05) enhanced the rate of wound contraction as compared to the control group at 21 days post burn. Faster epithelialization was also seen in the Honey Hydrogel treated group as compared to the other groups, although this was not statistically significant. The results substantiate the potential efficacy of Honey Hydrogel in accelerating burn wound healing.